Characterization of products from fast and isothermal hydrothermal liquefaction of microalgae. Issue 3 (22nd January 2016) - Faeth, Julia L.; Savage, Phillip E.; Jarvis, Jacqueline M.; McKenna, Amy M.; Savage, Phillip E.
Abstract : We investigated nonisothermal (fast) and nominally isothermal hydrothermal liquefaction (HTL) of Nannochloropsis sp. microalgae for the production of biocrude. Biocrude yields ranged from 36 to 45 wt % (dry weight), with fast HTL with low mass loading giving the highest yield. This condition also gave the biocrude with the lowest heating value, which indicates there are compromises to be made between biocrude quantity and quality. The aqueous phase and biocrude product fractions were characterized using elemental analysis and Fourier transform ion cyclotron resonance mass spectrometry (FT‐ICR MS). This detailed level of analysis identified more than 30, 000 unique molecular products. The aqueous phase products included compounds with the same molecular formulae as known herbicides, which may inform efforts in genetic engineering of algae and/or bacteria for cultivation on the aqueous phase. This detailed molecular‐level characterization provides some clues regarding the types of reactions that may take place during HTL. © 2016 American Institute of Chemical Engineers AIChE J, 62: 815–828, 2016